2019
DOI: 10.1007/s13593-019-0579-x
|View full text |Cite
|
Sign up to set email alerts
|

Vermicompost significantly affects plant growth. A meta-analysis

Abstract: Food production and waste management are two increasing issues ensuing from the growing world population. Recycling organic residues into amendment for food production seems to appear as an opportunity to partially solve this double challenge. Vermicomposting is a process whereby earthworms transform organic residues into compost that can be used as a substrate for plant growth. Many studies have evaluated the effect of vermicompost on plant growth, but a quantitative summary of these studies is still missing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 41 publications
5
67
0
6
Order By: Relevance
“…These variations in functional diversity of the bacterial communities over the course of vermicomposting could provide a plausible microbial-derived mechanism by which improved plant performance occurs when grown in vermicompost [12,57,58,59]. In line with this, Song et al [58] found that adding vermicompost enhanced the beneficial effects of plant growth-promoting rhizobacteria on both soil and crop, but the extent of this promotion varied with the dose of vermicompost and the crop type.…”
Section: Discussionmentioning
confidence: 99%
“…These variations in functional diversity of the bacterial communities over the course of vermicomposting could provide a plausible microbial-derived mechanism by which improved plant performance occurs when grown in vermicompost [12,57,58,59]. In line with this, Song et al [58] found that adding vermicompost enhanced the beneficial effects of plant growth-promoting rhizobacteria on both soil and crop, but the extent of this promotion varied with the dose of vermicompost and the crop type.…”
Section: Discussionmentioning
confidence: 99%
“…While the influence of plants on soil microbial communities is well documented (e.g. Philippot et al, 2013), the overlooked role of earthworms may be as important (Brown et al 2004;de Menezes et al 2018;Blouin et al 2019;Medina-Sauza et al 2019), given they represent the largest soil animal biomass in most terrestrial ecosystems (Bouché 1972). Indeed, root microbiota are renowned for their importance on plant health (Tkacz & Poole 2015;Pérez-Jaramillo et al 2016;Finkel et al 2017), but so far very few is known regarding the role of microbes leaving in contact with earthworms (Medina-Sauza et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it may provide a means to neutralize the pH of this winery byproduct, as previously shown by Domínguez et al [2]. And, on the other hand, vermicomposting has been shown to effectively reduce organic biomass and generate high-quality fertilizer with beneficial effects on soil and plants [18,19].…”
Section: Introductionmentioning
confidence: 94%